Stigmatization experiences of healthcare workers in the context of the COVID-19 pandemic: a scoping review - Reza Negarandeh; Mehraban Shahmari; Leily Zare (BMC, 2024)
Abstract Background During the COVID-19 pandemic, healthcare workers face the stigmatization of those caring for COVID-19 patients, creating a significant social problem. Therefore, this study investigated the stigmatization of healthcare workers in the context of the COVID-19 pandemic. Methods In this scoping review study, searches were conducted from December 2019 to August 2023 in Persian and English using various databases and search engines including PubMed (Medline), Embase, Scopus, ISI Web of Science, ProQuest, Science Direct, Springer, Cochrane Library, Google Scholar, and national databases. The study used English keywords such as Social Stigma, Health Personnel, Healthcare Worker, Medical Staff, Medical Personal, Physicians, doctors, Nurses, nursing staff, COVID-19, and coronavirus disease 2019, and their Persian equivalents, and their Persian equivalents to explore healthcare workers' experiences of COVID-19-related stigma. Results From a total of 12,200 search results, 77 eligible studies were included in this study. stigmatization of healthcare workers caring for COVID-19 patients was evident from the literature because of fear, misinformation, and negative self-image. Manifestations were violence and deprivation of social rights, resulting in adverse biopsychosocial, occupational, and economic consequences. This condition can affect negatively health staff themselves, their families, and society as well. Anti-stigmatization measures include informing society about the realities faced by healthcare workers, presenting an accurate and empathetic image of health workers, providing psychosocial support to health workers, and encouraging them to turn to spirituality as a coping mechanism. There are notable research gaps in comprehending the phenomenon, exploring its variations across diverse healthcare roles and cultural contexts, examining its long-term effects, and monitoring shifts in stigma perceptions over time. Conclusion The COVID-19 pandemic has resulted in the stigmatization of healthcare workers, causing mistreatment and rights violations. This stigma persists even post-pandemic, posing a psychological dilemma for caregivers. Addressing this requires comprehensive strategies, including tailored stigma prevention programs and research to understand its psychological impact.